UPAYA MEMINIMALISASI DISKALKULIA PADA SISWA KELAS 7G DI SMP NEGRI 2 KARTASURA - Lia Kusuma Jati; Muhammad Ponco Prasetyo; Nurul Shalihah; Titik Asmawati (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
This article discusses the existence of disease or dyscalculatic problems experienced by junior high school students, especially in the 7G grade. This research was conducted at SMP Negeri 2 Kartasura. The background of this research is the difficulty of students in understanding the basic concepts of mathematics. Diskalkulia is a form of learning difficulties experienced by children in learning mathematics. In fact, almost all students say that mathematics is the most difficult subject. If it's not difficult that means it's not math. Given the importance of mathematics in science and technology, it is only natural that mathematics becomes a compulsory subject that needs to be mastered and well understood by students in schools. The need for current and future mathematical applications is not only for everyday use, but especially in the world of work, and to support science.The cause of learning difficulties in mathematics is a common problem that often occurs in children in schools, with different types and different levels of difficulty. Problems experienced by students to understand the basic concepts of mathematics are influenced by several factors including internal factors of students who consider mathematics difficult, lack of student interest in learning mathematics. Whereas external factors include, the method used by the teacher in delivering material is less interesting so students feel bored when learning takes place.